The paradox of Velasquismo: union movement's opposition to the military dictatorship - Rospigliosi, Fernando (1988)
General Velasco's government was one of the most generous to Peruvian workers, but still, unlike other populist government in the region, it was unable to coopt them. This study contends there were there reasons for Velasco's failure: 1),  The institutional character of the military government; 2),  the role of middle-class radical elite which disputed the conduction of the workers movement to the military; and 3),  the short-lived expansive period of the economy.During the "second phase" of the military government, the unions played a key role for the retreat of the military, favoring at the same time the incorporation of leftist parties to the political system.